Diseño de un aerogenerador para suministro de energía eléctrica para el alumbrado nocturno-externo de la planta Vidrio Andino S.A. (2017)
In the present project the design of a wind generator was realized for supply of electrical energy for the night system of illumination - external of the Vidrio Andino S.A factory, it is located in Km 6.5 Route Soacha - Mondoñedo, Path Canoas, where in the first instance the wind resource of the zone was studied, then based on the current technology of the wind turbines there were defined three (3) alternatives of design focused in the type of structure of the wind turbine, it was selected and designed most adapted under the conditions established to replace part of the demand of electric power of the factory, and later there was verified the design selected by means of the method of finite elements. Other components of the wind turbine were selected and there were elaborated planes of location, manufacture and assemble of the wind turbine, as the manuals of operation, assembly and maintenance. On having had proposed the design of a wind turbine, not only there tries to diminish the environmental impact generated by the use of natural resources on the part of the factory Vidrio Andino, but also to offer new bases and to promote the use of renewable energies in the Colombian industry; for this reason, there was not evaluated the environmental impact that it brings the manufacture of the machine. Finally, a financial evaluation was realized to assure the viability of the project.